Cerebral autoregulation, beta amyloid, and white matter hyperintensities are interrelated. (10th April 2015) - Brickman, Adam M.; Guzman, Vanessa A.; Gonzalez-Castellon, Miguel; Razlighi, Qolamreza; Gu, Yian; Narkhede, Atul; Janicki, Sarah; Ichise, Masanori; Stern, Yaakov; Manly, Jennifer J.; Schupf, Nicole; Marshall, Randolph S.
Highlights: Vascular risk factors are associated with risk for Alzheimer's disease. We examined cerebral autoregulation, cerebrovascular disease, and amyloid in older adults. The three factors correlated with each other. Autoregulation, cerebrovascular disease, and amyloid pathology are interrelated. Abstract: Emerging studies link vascular risk factors and cerebrovascular health to the prevalence and rates of progression in Alzheimer's disease (AD). The brain's ability to maintain constant blood flow across a range of cerebral perfusion pressures, or autoregulation, may both promote and result from small vessel cerebrovascular disease and AD-related amyloid pathology. Here, we examined the relationship among cerebral autoregulation, small vessel cerebrovascular disease, and amyloid deposition in 14 non-demented older adults. Reduced cerebral autoregulation, was associated with increased amyloid deposition and increased white matter hyperintensity volume, which, in turn were positively associated with each other. For the first time in humans, we demonstrate an interrelationship among AD pathology, small vessel cerebrovascular disease, and cerebral autoregulation. Vascular factors and AD pathology are not independent but rather appear to interact.